2000
DOI: 10.1890/0012-9658(2000)081[3274:isssrl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Is Small-Scale Species Richness Limited by Seed Availability or Microsite Availability?

Abstract: To evaluate the relative roles of seed availability and competitive interactions in creating within-community patterns of species richness in unproductive grassland, we conducted a sowing experiment in a dry calcareous (alvar) grassland, where both the number of arriving seeds and the number of arriving species were approximately doubled compared to the natural seed rain. Also, in half of the plots, 36% of the vegetation and bryophyte cover was removed to simulate disturbance. Sowing significantly increased sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(124 citation statements)
references
References 77 publications
11
109
2
2
Order By: Relevance
“…Various experiments have shown that the limited availability of seeds is the principal reason for the weak regeneration of grasslands. The dispersal of most grassland species is limited to several metres or even to several dozen centimetres (Verkaar et al 1983;Stampfli and Zeiter 1999;Kalamees and Zobel 2002 and Fernández-Palacios 1995;Stampfli and Zeiter 1999;Kupferschmid et al 2000;Zobel et al 2000). Our results agree with earlier studies implying that in contrast to the initial colonisation of new sites, where stochastic processes are more important and species life-history traits are of little importance, later spread of species in developing grasslands strongly depend upon their life-history traits and becomes a function of time and management (cf.…”
Section: Discussionsupporting
confidence: 91%
“…Various experiments have shown that the limited availability of seeds is the principal reason for the weak regeneration of grasslands. The dispersal of most grassland species is limited to several metres or even to several dozen centimetres (Verkaar et al 1983;Stampfli and Zeiter 1999;Kalamees and Zobel 2002 and Fernández-Palacios 1995;Stampfli and Zeiter 1999;Kupferschmid et al 2000;Zobel et al 2000). Our results agree with earlier studies implying that in contrast to the initial colonisation of new sites, where stochastic processes are more important and species life-history traits are of little importance, later spread of species in developing grasslands strongly depend upon their life-history traits and becomes a function of time and management (cf.…”
Section: Discussionsupporting
confidence: 91%
“…However, sowing additional seeds on even undisturbed sites frequently does increase the number of established individuals of seeded species, indicating that there are more safe sites than seeds to fill them for some species in many communities (e.g. Tilman 1997;Turnbull et al 2000;Zobel et al 2000;Foster & Tilman 2003). These results suggest that likelihood of seed arrival does influence community structure in some communities, and more specifically support lottery-type models of species coexistence (McEuen & Curran 2004).…”
Section: Seed Limitation and Restorationmentioning
confidence: 59%
“…Numerically, the vast majority of individuals in temperate grasslands are a result of clonal propagation, with only a small percentage of individuals originating from seeds (Rusch & van der Maarel 1992;Zobel et al 2000;Benson & Hartnett 2006). Clonally propagated offspring (ramets) are placed at a widely varying, species-specific distance from the mother plant, and this distance has been shown to explain betweenspecies variation in the degree of conspecific aggregation (Turkington & Harper 1979;Lovett Doust 1981;McLellan et al 1997;Benot et al 2013).…”
Section: Introductionmentioning
confidence: 99%